Health effects of exposure to indoor volatile organic compounds from 1980 to 2017: A systematic review and meta‐analysis. (18th May 2022) - Liu, Ningrui; Bu, Zhongming; Liu, Wei; Kan, Haidong; Zhao, Zhuohui; Deng, Furong; Huang, Chen; Zhao, Bin; Zeng, Xiangang; Sun, Yuexia; Qian, Hua; Mo, Jinhan; et al.
Abstract: Exposure to volatile organic compounds (VOCs) indoors is thought to be associated with several adverse health effects. However, we still lack concentration–response (C‐R) relationships between VOC levels in civil buildings and various health outcomes. For this paper, we conducted a systematic review and meta‐analysis of observational studies to summarize related associations and C‐R relationships. Four databases were searched to collect all relevant studies published between January 1980 and December 2017. A total of 39 studies were identified in the systematic review, and 32 of these were included in the meta‐analysis. We found that the pooled relative risk (RR) for leukemia was 1.03 (95% CI: 1.01–1.05) per 1 μg/m 3 increase of benzene and 1.25 (95%CI: 1.14–1.37) per 0.1 μg/m 3 increase of butadiene. The pooled RRs for asthma were 1.08 (95% CI: 1.02–1.14), 1.02 (95% CI: 1.00–1.04), and 1.04 (95% CI: 1.02–1.06) per 1 μg/m 3 increase of benzene, toluene, and p ‐dichlorobenzene, respectively. The pooled RR for low birth weight was 1.12 (95% CI: 1.05–1.19) per 1 μg/m 3 increase of benzene. Our findings provide robust evidence for associations between benzene and leukemia, asthma, and low birth weight, as well as for health effects of some other VOCs.